Study the Efficiency of Irrigation in Rice Field Efforts to Increase Rice Yield in Irrigation Area Krueng Jrue - Rahmi Putri Yanti; Alfiansyah Yulianur; Maimun Rizalihadi (Syiah Kuala University, 2012)
Irrigation water management problems will arise if there is a shortage of waterin rice fields. Shortage of water in rice fields can be evaluated by the efficiency of existing irrigation.Based on the Indonesian‟s irrigation design criteria 65%, the project efficiency for Irrigation Planning is 65%. This value when compared to some countries in Asia was still much greater. This might be caused by undeterminating the water losses in the rice field. The study aims to determine the efficiency of irrigation in rice fields (Field Application Efficiency) is actually through direct measurements in the field, started at the land preparation up to the growth of rice plants. Measurements were taken at one tertiary JKr21Kr in Krueng Jreue Irrigation Region. To evaluate the efficiency of irrigation in ricefields used two methods of measurement. Inflow-outflow method for measuring the delivery of irrigation water in rice fields (Vf) which use the modified pipes that serves as the entrance and exit of water in the tertiary, the difference between incoming water and outgoing water is the amount of water used in rice fields. Water balance in the field is measured using Drum technique method with a diameter of 50 cm and height 125 cm. The drums are planted in the ground and a quarter of the height of the drum located above thesurface. By this equipment, the evapotranspiration parameters, percolation and effective rainfall can be obtained. These results showthat the efficiency of irrigation in rice fields (Ea) of 65.29%. It means that actually the project efficiency is 42.44% far below than Indonesian‟s criteria.